Transfer of dry-land resistance training modalities to swimming performance - Sadowski, J.; Mastalerz, A.; Gromisz, W. (Journal of Human Kinetics, 2020)
A great number of studies focusing on the effects of dry-land resistance training interventions on swimming performance remain inconclusive. It is suggested that transferability of dry-land strength gains to swimming performance appear when dry-land resistance training programs are swim-specific. The main aim of this study was to compare the effects of specific dry-land resistance training on an ergometer with traditional dry-land exercises, and to determine how much of the resistance training effects were transferred to specific swimming conditions. The study included a group of 26 youth competitive male swimmers (age 15.7 ± 0.5 years, height 174.6 ± 6.6 cm, weight 68.4 ± 8.2 kg, training experience 5.8±0.7 years) of regional level. They were randomly allocated to one of two groups: experimental (E) and control (T). Both groups were involved in a 12-week dry-land resistance training concentrated on increasing muscular strength and power output of the upper limbs. Group E used a specialized ergometer (JBA - Zbigniew Staniak), while group T performed traditional resistance exercises. The program consisted of 10 sets of 30 s of exercise with 30 s rest intervals between each set. A two-way repeated measures ANOVA with Tukey HSD post hoc comparisons was used to determine if any significant differences existed between training groups across pretest and posttest conditions. The significance level was set at p = 0.05. Dry-land resistance training modalities were the only differences in training between both groups. Our findings show that rates of transfer are much higher in group E than in group T, which resulted in a significant increase in swimming velocity (by 4.32%, p<0.001; ES=1.23, and 2.78%, p<0.003, ES=0.31, respectively).